Aramchol downregulates stearoyl CoA-desaturase 1 in hepatic stellate cells to attenuate cellular fibrogenesis - Bhattacharya, Dipankar (JHEP Rep, 2021)
BACKGROUND & AIMS: Aramchol is a fatty acid-bile acid conjugate that reduces liver fat content and is being evaluated in a phase III clinical trial for non-alcoholic steatohepatitis (NASH). Aramchol attenuates NASH in mouse models and decreases steatosis by downregulating the fatty acid synthetic enzyme stearoyl CoA desaturase 1 (SCD1) in hepatocytes. Although hepatic stellate cells (HSCs) also store lipids as retinyl esters, the impact of Aramchol in this cell type is unknown. METHODS: We investigated the effects of Aramchol on a human HSC line (LX-2), primary human HSCs (phHSCs), and primary human hepatocytes (phHeps). RESULTS: In LX-2 and phHSCs, 10 μM Aramchol significantly reduced SCD1 mRNA while inducing PPARG (PPARγ) mRNA, with parallel changes in the 2 proteins; ACTA2, COL1A1, β-PDGFR (bPDGFR) mRNAs were also significantly reduced in LX-2. Secretion of collagen 1 (Col1α1) was inhibited by 10 μM Aramchol. SCD1 knockdown in LX-2 cells phenocopied the effect of Aramchol by reducing fibrogenesis, and addition of Aramchol to these cells did not rescue fibrogenic gene expression. Conversely, in LX-2 overexpressing SCD1, Aramchol no longer suppressed fibrogenic gene expression. The drug also induced genes in LX-2 that promote cholesterol efflux and inhibited ACAT2, which catalyses cholesterol synthesis. In phHeps, Aramchol also reduced SCD1 and increased PPARG mRNA expression. CONCLUSIONS: Aramchol downregulates SCD1 and elevates PPARG in HSCs, reducing COL1A1 and ACTA2 mRNAs and COL1A1 secretion. These data suggest a direct inhibitory effect of Aramchol in HSCs through SCD1 inhibition, as part of a broader impact on both fibrogenic genes as well as mediators of cholesterol homeostasis. These findings illustrate novel mechanisms of Aramchol activity, including potential antifibrotic activity in patients with NASH and fibrosis. LAY SUMMARY: In this study, we have explored the potential activity of Aramchol, a drug currently in clinical trials for fatty liver disease, in blocking fibrosis, or scarring, by hepatic stellate cells, the principal collagen-producing (i.e. fibrogenic) cell type in liver injury. In both isolated human hepatic stellate cells and in a human hepatic stellate cell line, the drug suppresses the key fat-producing enzyme, stearoyl CoA desaturase 1 (SCD1), which leads to reduced expression of genes and proteins associated with hepatic fibrosis, while inducing the protective gene, PPARγ. The drug loses activity when SCD1 is already reduced by gene knockdown, reinforcing the idea that inhibition of SCD1 is a main mode of activity for Aramchol. These findings strengthen the rationale for testing Aramchol in patients with NASH.